Social And Psychological Considerations Of The Glottal Stop Status In Jordanian Arabic - Hammoudi, Khadidja (جامعة الوادي - University of Eloued, 2021)
The present study approaches studying the status of the variable (qàf) and its dialectal realizations in the Jordanian city of Amman. The nucleus of the research concentrates on the dialectal realizations of (q) including the urban [ʔ] and the rural [g]. In addition to our focus on the process of dialect contact, our profound province is to shed light on the main motives which make the natives accommodate to and adopt the outsider's variety mainly the urban Palestinian. The study brings the result that in a search for power and social status, gender proves to have a big influence on shifting and retention. Age also plays a significant role in parallel with origins and ancestry for the fact that old people are preservative and youngsters work for linguistic transition especially when influenced by other environments than the family.
Articl
Keywords: Amman ; dialect change ; glottal stop ; social and psychological factors